Microbiomes in respiratory health and disease: An Asia‐Pacific perspective. Issue 2 (February 2017) - Chotirmall, Sanjay H.; Gellatly, Shaan L.; Budden, Kurtis F.; Mac Aogain, Micheál; Shukla, Shakti D.; Wood, David L.A.; Hugenholtz, Philip; Pethe, Kevin; Hansbro, Philip M.
ABSTRACT: There is currently enormous interest in studying the role of the microbiome in health and disease. Microbiome's role is increasingly being applied to respiratory diseases, in particular COPD, asthma, cystic fibrosis and bronchiectasis. The changes in respiratory microbiomes that occur in these diseases and how they are modified by environmental challenges such as cigarette smoke, air pollution and infection are being elucidated. There is also emerging evidence that gut microbiomes play a role in lung diseases through the modulation of systemic immune responses and can be modified by diet and antibiotic treatment. There are issues that are particular to the Asia‐Pacific region involving diet and prevalence of specific respiratory diseases. Each of these issues is further complicated by the effects of ageing. The challenges now are to elucidate the cause and effect relationships between changes in microbiomes and respiratory diseases and how to translate these into new treatments and clinical care. Here we review the current understanding and progression in these areas.